REVIEW: THE RELATIONSHIP BETWEEN KNOWLEDGE AND MEDICATION ADHERENCE IN TYPE 2 DIABETES PATIENTS - Puspitasari, Neneng Eva; Wahyuningsih, Sri (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Diabetes mellitus poses a major threat to human health, as evidenced by the increasing prevalence of diabetes, and the number of cases of diabetes in Indonesia is anticipated to rise from 10.7 million in 2019 to 13.7 million by 2030.The lack of public knowledge and compliance with treatment has caused the incidence of the disease to increase every year. This Review aimed to determine the relationship between knowledge of medication compliance in patients with type 2 diabetes mellitus. The primary data methods obtained were national and international journals using search engines such as Google Scholar, PubMed, and Science Direct, as well as other search engines with the Narrative Review pattern. The search result of the publications obtained 769 articles; 40 articles screened full text based on the results of the screening that received 18 articles that met the inclusion criteria and were used as a review. The analysis of data writing in this article is mostly based on cross-sectional study approaches. Surveys were conducted within a three-month period. The results showed that knowledge had a significant relationship with drug consistency (p-value value = 0, 000 < 0.05). Knowledge is very much related to the medication compliance of each individual; the higher a person's knowledge, the better the attitude of compliance with diabetes drug consumption. Keywords: Compliance, Knowledge, Type 2 Diabetes, Narrative Review.